2012
DOI: 10.1515/dema-2013-0413
|View full text |Cite
|
Sign up to set email alerts
|

Closedness of certain classes of functions in the topology of uniform convergence

Abstract: In this paper, closedness of certain classes of functions in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is well-known (e.g., [13], p. 227-229) that, for Y a uniform space, C(X, Y ) is U X -closed in F (X, Y ) but not necessarily U p -closed. Later, some authors also obtained variants of these results for some other classes of functions, not necessarily continuous [11,16,34]. In this section, we establish some results for the class C α (X, Y ) of all "α-continuous" functions from X into Y [21,16].…”
Section: Remark 24 We Can Also Define the T λ -Open Topologies On C(x Y ) By Taking The Collection {Nmentioning
confidence: 66%
See 1 more Smart Citation
“…It is well-known (e.g., [13], p. 227-229) that, for Y a uniform space, C(X, Y ) is U X -closed in F (X, Y ) but not necessarily U p -closed. Later, some authors also obtained variants of these results for some other classes of functions, not necessarily continuous [11,16,34]. In this section, we establish some results for the class C α (X, Y ) of all "α-continuous" functions from X into Y [21,16].…”
Section: Remark 24 We Can Also Define the T λ -Open Topologies On C(x Y ) By Taking The Collection {Nmentioning
confidence: 66%
“…In section 2, we study their comparability and also coincidence of such topologies; we also discuss their existence and their relationship with some uniform convergence topologies. In section 3, we establish some results on closedness and completeness of the space C α (X, Y ) of all α-continuous functions, from X into Y [16,21]. Here, we shall need to assume that Y is a regular topological space, which is equivalent to Y being a locally symmetric quasi-uniform space [6,25].…”
Section: Introductionmentioning
confidence: 99%
“…Later, some authors obtained variants of these results for spaces of quasi-continuous, somewhat continuous and bounded functions in the case of Y a uniform space [16,22,37,40]. In this section, we examine their U A -closedness and right K-completeness in the setting of Y a locally symmetric quasi-uniform or locally uniform spaces.…”
Section: Closedness and Completeness In Function Spacesmentioning
confidence: 98%
“…In the same vein, Hoyle [10] showed that the set SW(X, Y) of all somewhat continuous functions from a space X into a uniform space Y is closed in Y X in the topology of uniform convergence. Furthermore, Kohli and Aggarwal in [14] proved that the function space SC(X, Y ) of quasicontinuous ( ≡ semicontinuous) functions, C α (X, Y ) of α-continuous functions, and L(X, Y) of cl-supercontinuous functions are closed in Y X in the topology of uniform convergence. In this section we strengthen the results of [14] and show that the set [32] if for each x ∈ A there exists a clopen set H such that…”
Section: Function Spacesmentioning
confidence: 99%